Strategi Meningkatkan Hasil dan Kualitas Temulawak (Curcuma xanthorrhiza) di Bawah Pohon Jati (Tectona grandis) - Nihayati, Ellis; Rizqullah, Dellia Rezha Bayu; Widaryanto, Eko (Jurnal Hortikultura Indonesia, 2021)
Temulawak (Curcuma xanthorrhiza Roxb.) can grow on dry land that is planted with trees or perennials. Temulawak intensification can potentially use the lands planted with teak trees as there is wide space available to grow temulawak or other gingers between the trees. Planting distance of Temulawak under the teak trees will affect the growth, quality, and quantity of temulawak. The purpose of this research is to study and obtain the optimal planting distance of temulawak grown under the teak trees to obtain better growth and maximum yields. The study was carried out from December 2019 to June 2020 in the experimental field of Brawijaya University at Jatikerto Village, Malang Regency. The experiment was set up in a  split-plot design consisted of 2 main plots, i.e. 3-year-old and 17-year-old teak trees, and planting distances as subplots, i.e. 50 cm × 50 cm (J1), 50 cm × 40 cm (J2), 50 cm × 30 cm (J3), 50 cm × 20 cm (J4). All treatments had 4 replications. From the results of the study, it was found that planting temulawak under the 3-year-old teak trees at a spacing of J1 resulted in the optimum weight of temulawak rhizomes per hectare. The optimum quality of temulawak in terms of the antioxidant activity level is found in temulawak planted under 17-year-old teak trees with the spacing of J4. The highest light intensity was found in temulawak planted underneath the 17-year-old teak trees.Keywords: antioxidants, curcumin, light intensity, plant spacing